Identificação do cronotipo e sua interferência no desempenho cognitivo de adolescentes: sequência didática em cronobiologia - Thiago Moreira Batista (2022)
This paper describes an instructional sequence for presenting chronobiology to high school students. In order to achieve the purpose of the sequence, investigative methodologies were used to motivate the students to be protagonists of constructing their own knowledge, at the same time that they were encouraged to build hypothesis and solve problem situations. Chronobiology is a field in Science that studies biological rhythms. Most of living creatures present daily cycles and rhythms which are called circadian rhythms and cause specific effects in their lives. All these cycles and rhythms determine our way of living, the hours we wake up, eat, go to bed, among other daily activities. The main concepts of chronobiology were presented and discussed, allowing the students to recognize their chronotypes (morningness, intermediate-type or eveningness), seeing the chronotypes as a personal profile used by biological regulation processes. The chronotype groups were established based on specific questionnaires like “Sleep Journal”, the “The Munich Chronotype Questionnaire” and the “Morningness-Eveningness Questionnaire”. Later on, those results were associated with academic performance, evaluating their circadian rhythms. Applying the knowledge of chronobiology to people’s lives contributes to their growth and important decision-making processes, since it gives them the chance to organize their work/study schedule in a way to guarantee a better performance. Carrying out this research made it possible to promote situated learning, which developed the students’ argumentative skills through data collection and analysis, as well as through analysis of demographic charts. Another outcome of this experience was the production of teaching material to be presented to the school community.